Endoscopic Ultrasound-guided Fine-needle Aspiration Biopsy of a Renal Mass - Jaehyun Ha; Daejin Kim; Hyunsoo Kim; Chang Keun Park; Jaekwon Jung; Yun Jin Chung; Jaekwang Lee; Hanjun Ryu (Yong Chan Lee, 2021)
Traditionally, tissue biopsies of kidney lesions are usually performed with CT or percutaneous ultrasound guidance, but biopsies using EUS have rarely been reported. In this report, we describe a case of renal cell carcinoma (RCC) diagnosed using EUS-guided fine-needle aspiration biopsy. A 75-year-old woman taking aspirin due to stable angina continued to exhibit weight loss and anemia and visited the gastroenterology department. No bleeding was observed on upper and lower gastrointestinal endoscopy. A contrast-enhanced mass was observed in the left kidney, accompanied by 8.9×10.8 cm-sized necrosis suggesting RCC on abdominal CT. Chest CT showed masses in both lungs. We planned to administer targeted therapy after pathological confirmation using EUS. Aspirin was continued, and we performed fine-needle biopsy using a 22-gauge needle three times. No adverse events were observed after the procedure. Pathological examination confirmed RCC, clear cell type, and the patient is currently undergoing treatment with sunitinib. EUS-guided fine-needle aspiration biopsy is safe for liver, pancreatic, or other tumors accessible from the upper gastrointestinal tract. This technique shows fewer adverse events. To the best of our knowledge, there have been no other reports on EUS-guided fine-needle aspiration biopsy to identify RCC in Korea.